The extent to which Islamic science teachers use the strategy of individualization of education, its methods, and the obstacles that limit its application - Al- Hatem, Monerah Hamad; Al- Saif, Abdulmohsen Saif (Journal of Educational and Psychological Sciences, 2021)
The study aimed to know the extent of the use of forensic science teachers to methods of individualizing education, The extent of their knowledge of this strategy, and the obstacles to its use, this study was applied to the forensic science teachers in the middle stage, In the general education schools in Layla affiliated to Al- Aflaj Governorate, during the first semester of the year 1441- 1442 AH, whose number is (18) female teachers, The researcher used the descriptive method, The questionnaire was used to collect data, The data was analyzed using SPSS, and the results indicated that there is a dearth of training courses in this strategy, It also indicated that 94.4% of the teachers do some unique methods, such as choosing the most appropriate means of reinforcement for the desired behavior, And pause a little to make sure the student understands the skill, and develop a treatment plan for the underachieved students and arouse the enthusiasm of the students for active participation, Also, the increase in the teaching quorum is the most important obstacle that affects the application of methods.
Keywords: individualizing education; Intermediate stage; Islamic education